Root Apex Transition Zone As Oscillatory Zone - Baluška, František; Mancuso, Stefano (Frontiers in Plant Science, 2013)
Root apex of higher plants shows very high sensitivity to environmental stimuli. The root cap acts as the most prominent plant sensory organ; sensing diverse physical parameters such as gravity, light, humidity, oxygen and critical inorganic nutrients. However, the motoric responses to these stimuli are accomplished in the elongation region. This spatial discrepancy was solved when we have discovered and characterized the transition zone which is interpolated between the apical meristem and the subapical elongation zone. Cells of this zone are very active in the cytoskeletal rearrangements, endocytosis and endocytic vesicle recycling, as well as in electric activities. Here we discuss the oscillatory nature of the transition zone which, together with several other features of this zone, suggest that it acts as some kind of command centre. In accordance with the early proposal of Charles and Francis Darwins, cells of this root zone receive sensory information from the root cap and instruct the motoric responses of cells in the elongation zone.